Pengaruh Model Kooperatif Learning Tipe STAD Terhadap Kemampuan Numerasi Siswa Kelas 5 SD Negeri Pujerbaru 02 - Fakhri Fakhruddin Anwar Anwar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
Mathematics as one of the compulsory subjects taught from elementary school to university level. One of the goals of mathematics subjects taught at the elementary school level is to equip students to become independent learners and able to find mathematical concepts that can be used in solving problems that arise in everyday life. And the purpose of this research is to improve students' numeracy skills after being given the STAD (Student Teams Achievement Division) learning model. The methodology used in this study is a research instrument in the form of a question sheet given to students used for research data, and an assessment instrument given to students in the form of working on questions containing numeration, counting fractions, multiplication, subtraction and division where the research subject is are 5th grade students of SD Negeri Pujerbaru 02 as many as 6 children using 2 stages of research, namely pretest and posttest. The results of the study proved that using the STAD (Student Teams Achievement Division) model was successful and had a positive impact on increasing students' knowledge and numeracy skills in the classroom